Investigating the impact of linguistic and non-linguistic factors on EMI academic success. (July 2022) - Soruç, Adem; Pawlak, Mirosław; Yuksel, Dogan; Horzum, Barış
Abstract: English as a medium of instruction (EMI) has been extensively growing as a global phenomenon in higher education. This study investigates the predictive impact of mediating variables – non-linguistic factors (i.e., students' type of motivation, self-regulation skills, and self-efficacy) and linguistic factors (i.e., general English proficiency) – on EMI students' academic success in a Turkish higher education context. The participants ( n  = 459) were conveniently sampled from four partial EMI programmes: two from the social sciences and two from engineering ( n  = 218 and n  = 241 students, respectively). Using multi-item scales and different models of analysis, such as Structural Equation Modelling (SEM), in the measurement of linguistic and non-linguistic factors, the study revealed that except for the type of motivation, EMI students' individual characteristics, namely their self-regulation skills and sense of self-efficacy, play a significant role in their academic success regardless of the academic programme division. Besides, the analysis revealed that the type of motivation directly impacted language proficiency, which further predicted EMI students' academic success in both academic divisions. Finally, the comparison of the SEM models for both academic divisions indicated that the relationship between the type of motivation and language proficiency, and the relationship between self-regulation skills, self-efficacy, and academic success were higher in EMI programmes in social sciences when compared to those in Engineering programmes. These results are discussed, and pedagogical implications are given for the teaching/learning situations in EMI contexts. Highlights: EMI students' self-regulation skills and sense of self-efficacy predicted the students' academic success. EMI students' level of motivation did not predict their academic success but directly impacted their English language proficiency. English language proficiency predicted the students' academic success.